EXAMINING THE EFFECT OF SERVICE VALUE AND REPUTATION ON CUSTOMER LOYALTY WITH TRUST AND ELECTRONIC WORD OF MOUTH AS MEDIATION - Burhanudin, Burhanudin (Jurnal Aplikasi Manajemen, 2022)
To determine how banking services can lead to long-term profit, examining service value's direct and indirect effect on customer loyalty to the bank is essential. This study aims to investigate the effects of service value on customer loyalty to the bank directly and indirectly through the bank's reputation, electronic word of mouth (eWOM), and trust. This study surveyed 312 Indonesian banking customers by applying the partial least square structural equation model (PLS-SEM) to test the proposed hypotheses. This study found that the effect of service value on customer loyalty to the bank is indirect, not direct. Service value affects customer loyalty to the bank through trust and the bank's reputation. In addition, the bank's reputation affects customer loyalty to the bank through eWOM. Service value does not affect customer loyalty to the bank. This study addresses the past (represented by the bank's reputation as the firm's past action and eWOM as the customer's experience) and the future (represented by trust) to understand the relationship between service value and customer loyalty in the banking sector. The findings imply that banks need to develop their banking service value and reputation, trust, and eWOM to encourage customer loyalty to their banks.